Regional industrial path development: The role of new entrepreneurial firms - Jan Ole Rypestøl (Journal of Innovation and Entrepreneurship, 2017)
Entrepreneurs play an important role in the evolutionary process of regional industries. As founders of new firms, entrepreneurs increase the supply side of the industrial economy, and by doing so, they challenge the incumbent firms to respond. From the perspective of evolutionary economics, understanding these dynamics of entrepreneurial triggers and industrial firm responds are important, as it sheds new light to our understanding of how regional industries evolve. The entrepreneurship literature offers several classifications which are helpful in distinguishing between different types of entrepreneurs and firms. However, none of these classifications and typologies are suitable for explaining what effect new entrepreneurial firms may be expected to have on regional industries and their future development. This paper seeks to address this knowledge gap. Based on two dimensions, innovation novelty and entrepreneurial growth intention, the conceptual framework develops a typology of new entrepreneurial firms' expected effect on future regional industrial development. In doing so, the paper contributes to the field of evolutionary economic geography by introducing a new perspective on entrepreneurial firms' contribution to dynamic regional industrial path development.
Keywords: 650; Regional development; Entrepreneurship; Path dependency; Typology; Innovation novelty; Growth intentions